2013
DOI: 10.1515/cclm-2013-0166
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of EGFR autoantibodies in the amplification phenomenon of HER2 in breast cancer

Abstract: S-EGFRAb can be measured accurately using the ELISA we developed. We conclude that autoantibodies against EGFR do not seem to be associated with the HER2 gene amplification phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
(20 reference statements)
3
6
0
Order By: Relevance
“…In the current study, we found no correlation between the presence of autoantibodies and patient survival. Similar findings have been reported in ovarian and breast cancer [ 36 , 37 ] and may indicate that autoantibodies to zinc finger proteins are more suitable for diagnostic or screening purposes rather than disease prognosis.…”
Section: Discussionsupporting
confidence: 85%
“…In the current study, we found no correlation between the presence of autoantibodies and patient survival. Similar findings have been reported in ovarian and breast cancer [ 36 , 37 ] and may indicate that autoantibodies to zinc finger proteins are more suitable for diagnostic or screening purposes rather than disease prognosis.…”
Section: Discussionsupporting
confidence: 85%
“…FISH was used to detect the gene amplification status when HER-2 immunohistochemistry was + or ++. The results of EGFR, MMP-2, E-cadherin and N-cadherin were evaluated in line with the publication from Queiroga et al, Olsen et al, van Duijnhoven et al and Elzagheid et al [12][13][14][15].…”
Section: Methodssupporting
confidence: 55%
“…After excluding 579 non‐English articles and 1318 duplicates, 4441 articles not relevant to the topic and 58 meeting the exclusion criteria were excluded. Ultimately, 84 articles were included . A total of 196 specific tumour‐associated autoantibodies (Table S1) were reported, of which 23 specific tumour‐associated autoantibodies (Table ) had been studied more than once.…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly used detection method was ELISA (60 studies) (Table S1). Western blot [21,26,60,76,80,81,83,[87][88][89] or immunoprecipitation [74,87] was often used to confirm positive results. Twelve studies used only Western blot [30,33,36,45,46,51,57,62,75,85,92,97], and six studies used O-glycopeptide or autoantigen microarray [10,37,38,41,50,67] to detect the tumourassociated autoantibody.…”
Section: Tumour-associated Autoantibody Detection Methodsmentioning
confidence: 99%